Edukasi Pencegahan Stunting melalui Home Literacy Environment di Desa Jetis - Hariz Ilham Samhaji; Amardiana Rahayau, Atikah Dewi; Dewi, Wahyu Amalia; Dahlan Putra, Nugraha Putra; Prasandha, Diyamon (Universitas Negeri Semarang, 2024)
Stunting is characterized by conditions when children face growth delays, not only regarding height but also nutrition. This counseling activity is aimed at parents of toddlers, pregnant women, and adolescents with the aim that public awareness will increase after being educated on stunting prevention and control. This study uses a qualitative method by providing a real picture of the Home Literacy Environment (HLE) applied by parents in children's literacy development based on the results of observations of activities in the field. Counseling activities were carried out five times with 3 of them targeting parents of toddlers on December 13, 2023 in Jetis Kulon Hamlet, December 14, 2023 in Jetis Wetan Hamlet, and December 15, 2023 in Gerdu Hamlet. On December 22, 2023, it will be carried out in Pungkuk Hamlet with the target of Pregnant Women, while on December 23, 2023, it will be carried out in Gerdu Hamlet with the target of teenagers. The community enthusiastically participated in the counseling observed during the discussion.